Physiological and molecular comparative analysis of two contrasting rice varieties under jasmonic acid treatment - To, Huong Thi Mai; T. P. Mai, Nga; Anh Ngo, Minh; Huyen Nguyen, Ngan; Thi Hanh, Kieu; Trang Nguyen, Thi; Thi Thu Vu, Hien; Khanh Tran, Dang; Thi Van Le, Anh; Hieu Nguyen, Trang; et al. (Vietnam Journal of Biotechnology, 2020)
Rice is one of the most important crops but its productivity is severely threatened by both biotic and abiotic stresses. Jasmonic acid and its derivatives (referred to JA) are the lipid-based plant hormones that were commonly known as regulators of plant growth, development and defense responses. In this study, we compare the physiological and molecular responses of two rice accessions, G38 (Nep_nuong) and G11 (Tam-tron) to JA treatment. G38 plants under JA treatment experienced a reduction in shoot length, root weight, shoot weight and total plant weight which suggested its sensitiveness to JA, whereas G11 plants showed a less reduction in these traits. The expression levels of 12 JA-related genes were investigated in order to better understand how the JA biosynthesis and responses differ in these two contrasting rice accessions. A significantly higher expression level of a set of genes related to JA biosynthesis, signaling and response in G11 compare to G38 was observed. Furthermore, the inorganic phosphorus starvation (Pi) response was also examined in the two varieties G11 and G38. In low Pi condition (40 µM), G11 plants showed more roots, longer root length and shoot length, higher weight compared to the G38 plants which suggest that G11 did not suffer much effect of Pi deficiency. This study highlights the differences in JA growth response in 2 contrasting rice genotypes and also suggests the link between JA developmental response and the tolerance to the Pi starvation condition in rice.